The Teachings of Sattariyah Tariqa in Islamic Manuscripts in The National Library of Republic of Indonesia: Study of Text and Translation (Journal Intellectual Sufism Research (JISR), 2024)
Abstract. The Sattariyah order was originally spread in Aceh by a Sufi named Abdurrauf bin Ali al-Jawi al-Sinkli (d. 1693) in the 17th century, and in the following century the Sattariyah order spread from Aceh to Java. The objectives of this study include (1) To find out how philological studies are carried out on the texts of the teachings of the Sattariyah order contained in the national library, (2) To find out how the Sufi teachings contained in the texts of the Sattariyah order teachings. This study uses a qualitative data analysis method with philological theory and hermenological theory. The method is carried out through several stages, namely collecting text data, presenting data, reducing text, and drawing conclusions. The results of this study stated that the teachings of the sattariyah tarekat contained in the PNRI 628 manuscript contained the intention of prayer and other worship. Readings in prayer and after prayer, genealogy of the Sattariyah tariyah order, dhikr and intention of sunnah prayer, Wirid prayer, procedures for dhikr, various disciples, shahada problems, spirit, benefits of reading bismillah, praise and prayer problems, and self-problems.